Jambu, a new genus of tarantula from Brazil (Araneae, Theraphosidae, Theraphosinae) - Miglio, Laura T.; Perafán, Carlos; Pérez-Miles, Fernando (European Journal of Taxonomy, 2024)
The genus Jambu gen. nov. is proposed based on two new species: Jambu paru gen. et sp. nov. and Jambu manoa gen. et sp. nov. Hapalopus butantan is transferred to Jambu; consequently, Jambu butantan gen. et comb. nov. is proposed. The geographic distribution of J. butantan is extended on the basis of new material collected. The new genus and the new species are here diagnosed, described and illustrated. The shape of the genitalia of Jambu resembles that of Hapalopini but differs from most of them by the presence of type IV urticating setae. The presence of this type of urticating setae allows us to hypothesize that this new genus is phylogenetically related with Grammostolini. Males of Jambu differ from those of other genera of Grammostolini by the presence of a paraembolic apophysis on the palpal bulb. Females also differ from those of other Grammostolini by the spermathecae morphology, with one medial lamp-shaped or heart-shaped receptacle. The homology of some features and the taxonomic placement of the new genus are discussed.